Tidepools, Pacific Grove - Steven Domingo:::Photographer::::::::::::; Vinnie Lopez:::Photographer:::::::::::: (Pacific Grove, California)
Tidepool on the coast of Pacific Grove, California, south of the City of Monterey, Ed Ricketts searched the tidepools and shoreline here to collect specimens.